O currículo de Filosofia no Ensino Médio: em busca do diálogo entre os saberes abertos e os saberes específicos do campo filosófico - Dutra, Jorge da Cunha (2010)
This paper refers to a research which I developed on regular daytime public High Schools from Rio Grande city. The study aimed to investigate if female and male teachers of Philosophy promote dialogue between the open knowledge and specific knowledge to the field of Philosophy in their teaching practices. In order to achieve the proposed objective, 13 teachers from 10 schools were interviewed, and I also collected the syllabus. After finishing this investigation, I conclude that the presence of dialogue between the open knowledge and specific knowledge allows a change in female and male student‟s attitude with regard to behavior in the classroom, in society, involvement and responsibility in organization with the school environment and defining future prospects in their career choices. After all, I think new ways of teaching could be build, in a way that teaching could be close to the female and male student‟s lives, and became an effective area of historical and social construction.